Светлая моя любовь - Граубин Георгий Рудольфович (Экспресс-издательство, 2009)
Экземпляры: аб. ЦБ (20210325) / Инвентарный номер: 10784 / Цена: / Сис.шифр: 84(2=Рус)7 / Авт.знак: Г 77 / ББК: 84(2=Рус)7